Studies towards the total synthesis of a natural product alkaloid - Walker, Hetty Sadie (2023)
This thesis outlines work towards the optimisation and total synthesis of dehydromatrine [C], a quinolizidine alkaloid found in the root of the Sophora flavescens Aiton plant. Four steps [A-B] in the proposed total synthesis were successfully undertaken and each intermediate that was made was isolated and comprehensively analysed. Each individual step was optimised and enhanced to increase yield by changing solvents, reagents, or equivalents. This was pivotal as due to the total synthetic route having nine hypothesised steps at the start it was crucial that yield was preserved after each reaction. Aligning to this, different proposed synthetic routes had to be updated and changed depending on the feedback gained from each result as sometimes reactions did not work, and yield could not be improved greatly.When undertaking this research, the main aims were to ensure that the natural product was created from commercially available starting reagents and once made was analytically identical to the quinolizidine alkaloid [C], that had been extracted from the natural source.Several novel molecules [D-G] were successfully synthesised using a range of different strategies from the literature and conditions were changed accordingly. These reactions were developed and optimised so that the best possible yields could be attained.